Analysis of Flavonoid Levels in Extract of Gambas Fruit (Luffa acutangula L) Originating from the Village of Posona District Parigi Moutong - Aharudin Aharudin; Kasmudin Mustapa; Minarni R. Jura (Universitas Tadulako, 2020)
Gambas fruit (Luffa acutangula L) is a cultivable plant. Gambas fruit can be used as an alternative free radical antidote. The purpose of this study was to determine the level of flavonoids in extract of gambas fruit (Luffa acutangula L) originated from Posona village of Parigi Moutong Regency. This research uses UV-Vis spectrofotometry analysis method. Flavonoids test was done by extracting the sample using 1% HCl solvent in ethanol. The result of the experiment showed that flavonoid level on the fruit of gambas (Luffa acutangula L.) was young gambas 10.60 mg/100g and old gambas 2.62 mg/100g.